Compassion Focused Approaches to Working With Distressing Voices - Heriot-Maitland, Charles; McCarthy-Jones, Simon; Longden, Eleanor; Gilbert, Paul (Frontiers in Psychology, 2019)
This paper presents an outline of voice-hearing phenomenology in the context of evolutionary mechanisms for self- and social- monitoring. Special attention is given to evolved systems for monitoring dominant-subordinate social roles and relationships. These provide information relating to the interpersonal motivation of others, such as neutral, friendly or hostile, and thus the interpersonal threat, versus safe, social location. Individuals who perceive themselves as subordinate and dominants as hostile are highly vigilant to down-rank threat and use submissive displays and social spacing as basic defences. We suggest these defence mechanisms are especially attuned in some individuals with voices, in which this fearful-subordinate – hostile-dominant relationship is played out. Given the evolved motivational system in which voice-hearers can be trapped, one therapeutic solution is to help them switch into different motivational systems, particularly those linked to social caring and support, rather than hostile competition. Compassion Focused Therapy seeks to produce such motivational shifts. Compassion Focused Therapy aims to help voice-hearers, i) notice their threat-based (dominant-subordinate) motivational systems when they arise, ii) understand their function in the context of their lives, and iii) shift into different motivational patterns that are orientated around safeness and compassion. Voice-hearers are supported to engage with biopsychosocial components of compassionate mind training, which are briefly summarised, and to cultivate an embodied sense of a compassionate self-identity. They are invited to consider, and practice, how they might wish to relate to themselves, their voices, and other people, from the position of their compassionate self. This paper proposes, in line with the broader science of compassion and Compassion Focused Therapy, that repeated practice of creating internal patterns of safeness and compassion can provide an optimum biopsychosocial environment for affect-regulation, emotional conflict-resolution, and therapeutic change. Examples of specific therapeutic techniques, such as chair-work and talking with voices, are described to illustrate how these might be incorporated in one-to-one sessions of Compassion Focused Therapy.